Praziquantel Failure in the Treatment of Fasciola hepatica - David Michael Patrick; Judith Isaac-Renton (Canadian Journal of Infectious Diseases)
A case of human fascioliasis is presented in which the patient remained symptomatic after treatment with praziquantel and other agents but eventually responded to bithionol. The difficulties in finding an efficacious and tolerable drug therapy for this condition are reviewed with reference to the life cycle and pathogenesis of the parasite. It is concluded that while bithionol remains the current drug of choice, triclabendazole may play a dominant role in the near future.